LITERARY ARCHITECTURE - Gehlot, Kunika; Mishra, Soma Anil; Trivedi, Kavya (International Journal of Research -GRANTHAALAYAH, 2018)
Architecture and Literature are the social forms of art peculiar to the mankind. Architecture creates a story with a thread of spaces whereas Literature builds a visual representation of a place with words. They have been practiced together from ancient times in order to leverage the experience of users in their respective fields. The primary purpose of the research is to study the amalgamation of these domains of art in order to enhance the prospects of designing in a better-experienced way. Architects and Writers work on the same base with an alike goal and, Architectural concepts could be kindled and inspired by anything in the world henceforth, it could be stimulated by novels and narrations of literature. Thus, the result and conclusion would be exploring an exercise and posing an example of the novel The Fountainhead by Ayn Rand, manifested by the literature review and case studies, henceforth triggering the thoughts of future evolution and enhancement of practice on the topic